“Nationalistic Backlashes Along the Balkan Migrant Corridor” - Runcheva Tasev, Hristina (International Academic Institute, 2019)
The paper analyses the migrant influx in Europe, which has affected the national politics along the Balkan migrant and refugee corridor and European politics in general. It created a momentum for political actors to present the phenomenon of migration as a threat to national interests and ideals, cultural attitudes, social structures and demography etc. The moral duty to help others in need was replaced by the patriotic calls for defense of the nation-state. The influx of refugees and migrants in the EU has caused strong nationalistic backlashes in the transit and receiving states. The paper examines the reasons why the anti-immigration parties and movements, in general, have stronger presence in post-Soviet countries than in Western member states.
Keywords: Balkan; migrants; refugee corridor; nationalistic backlashes